The Increased Expression of HLA-DR and ICAM-1 Molecules by Human Bronchial Epithelial Cells, Induced by Activated Mononuclear Cells, is Downregulated by Nedocromil Sodium - O. Sacco; S. Lantero; L. Scarso; V. Frangova; V. Ottolini; G. A. Rossi (Mediators of Inflammation)
To test the hypothesis that mononuclear cell products could increase the expression of HLA-DR and ICAM-1 molecules in bronchial epithelial cells (BECs), subconfluent cultures of human BECs, obtained from surgically resected bronchi, were incubated with PHA-activated blood mononuclear cell conditioned media (BCM-CM) or recombinant IFN-γ. The presence of HLA-DR and ICAM-1 molecules on BECs was then evaluated by specific antibody staining and flow-cytometry analysis. The addition to BEC cultures of different concentrations of PHA-stimulated BMC-CM, or of IFN-γ induced a dosedependent increase of HIA-DR and ICAM-1 expression, while no effect was observed with unstimulated BMC-CM. The ability of nedocromil sodium and, as control, of dexamethasone, to prevent the upregulation of HLA-DR and ICAM-1 expression on BECs was then tested. Increasing concentrations (10−7 to 10−4 M) of nedocromil significandy inhibited HLA-DR and ICAM-1 expression by BECs in a dose-dependent fashion. A similarly dose-dependent inhibitory effect was also observed with dexamethasone, which, however, was less active than nedocromil on HL-ADR expression and more active on ICAM-1 expression. Finally, nedocromil and dexamethasone showed a significant synergistic effect on the expression of both cell surface molecules at the lowest concentrations tested.